Mutality in psychotherapy: a meta-analysis and meta-synthesis - Cornelius-White, J.; Kanamori, Y.; Murphy, David; Tickle, M. (American Psychological Association, 2018)
This manuscript presents a systematic review of mutuality in psychotherapy, including meta-analysis of quantitative and meta-synthesis of qualitative studies. A search with specified keyword combinations yielded 21 studies, including 10 quantitative studies with 1,071 participants and 11 qualitative studies with 81 participants. Researchers calculated effect sizes, conducted homogeneity tests, and assessed potential variables moderating the relationship between mutuality and therapeutic variables from quantitative studies; they analyzed qualitative studies to identify and synthesize themes related to mutuality in psychotherapy. Meta-analysis showed a large weighted mean effect size with a statistically significant overall relationship between mutuality and therapeutic variables (r = 0.51, 95% CI [0.37; 0.66], p < 0.001). The relationship between mutuality and session quality was strongest of the six relationships analyzed (r = 0.70, 95% CI [0.43; 0.97], p < 0.001). Qualitative meta-synthesis of studies produced six themes: 1. Lack of mutuality/strategies for disconnection, 2. Co-created relational process, 3. Meta-communication and misunderstanding, 4. Therapist congruence/being real, 5. Mutual impact and client agency, and 6. Asymmetric role power and boundaries. These findings suggest that mutuality is worthy of further research in psychotherapy, particularly in relation to its strong relationship with session quality.